FAKTOR-FAKTOR YANG MEMPENGARUHI KESEDIAAN MEMBELI PRODUK HIJAU - Siti Khoiriyah; Muh Juan Suam Toro (Jurnal Bisnis dan Manajemen (Journal of Business and Management), 2014)
This research has proposed a conceptual framework to investigate the antecedents of attitude toward green product and its effect on willingness to pay and intention to purchase. To test the conceptual framework, structural equation modelling (SEM) has been used to analyse the data collected from 200 women (young adult, educated, has children, interest to purchase of green product and independently have income). The investigated antecedents are health consciousness, environmental attitude, and value orientation. The results of this study indicate that health consciousness, environmental attitude, and value orientation have significant and positive influence on the attitude toward green product, subsequently the attitud toward green product influence the willingness to pay. The willingness to pay then will drive the customer’s purchase intention.